Polymer protective film and preparation method and application thereof
By introducing biomass materials such as starch and chitosan into the packaging materials, combined with multi-layer co-extrusion technology, a polymer protective film was designed, which solved the problems of existing packaging materials being prone to adsorbing dust, poor self-adhesion performance and poor degradation, and achieved the effects of self-adhesion, degradation and anti-fouling, reducing pollution and environmental impact at the construction site.
Patent Information
- Application Number
- CN202411887095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing packaging materials such as PE films are prone to adsorbing dust during road construction, have poor self-adhesion performance and poor degradation, resulting in construction site pollution and environmental impact.
A polymer protective film is designed, using multi-layer co-extrusion technology. The inner adhesive layer contains biomass materials such as starch and chitosan, which has good self-adhesion and degradability. The outer protective layer is smooth, sun protection and wrinkle-resistant.
It realizes the self-adhesive, degradable and anti-fouling properties of packaging materials, reduces pollution and environmental impact at the construction site, and reduces construction costs.
Smart Images

Figure CN119859475A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a polymer protective film, a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In the field of road construction, building materials are usually piled up outdoors. When exposed to the sun or rain, they need to be packaged or covered. In order to reduce costs, the main packaging material currently used on construction sites is PE film, which is economical and has a variety of models to choose from. However, PE film is also easy to absorb dust and has poor self-adhesive properties, and requires additional adhesives to help fix it.
[0004] In addition, the construction process also needs to use a film as a covering material. For example, in the current road construction, after the road base is completed, the curbstones are laid first, and then the asphalt is laid. For this reason, when laying asphalt, it is also necessary to cover and protect the curbstones with tape and plastic film to prevent asphalt from sticking. For example, patent CN212426611U provides an anti-sticking covering material for curbstones. The plastic film is fixed to the surface of the curbstone by a fixing part. After the asphalt is laid, the plastic film is torn off, and the part pressed under the asphalt can only be slowly degraded by microorganisms. The PE film has poor degradability, and the PE film left at the construction site is often difficult to degrade by itself. Summary of the invention
[0005] In view of the above situation, the inventors believe that providing a self-adhesive and degradable packaging material is of great significance for the outdoor protection of building materials and road construction. In order to simultaneously meet the performance requirements of the packaging material being easy to degrade and wrinkle-resistant, the present invention is designed to provide a polymer protective film material with different properties in the inner and outer layers. The inner layer in contact with the building material should have a certain degree of adhesion, be self-adhesive, and be able to adhere to the building material more firmly. The outer layer has a certain degree of smoothness and sun protection performance, can cope with the construction environment of sun and rain, reduce the adsorption of dust, and has a certain degree of wrinkle resistance, and is expected to be reused.
[0006] In order to achieve the above technical effects, the present invention provides the following technical solutions: According to a first aspect of the present invention, there is provided a polymer protective film, comprising an integrally formed adhesive layer and a protective layer; the raw material ratio of the adhesive layer is as follows: 150-170 parts of low-density polyethylene, 75-86 parts of starch, 8-11.2 parts of chitosan, and 2-6 parts of a cross-linking agent; the raw material of the protective layer comprises at least 240-260 parts of low-density polyethylene.
[0007] The adhesive layer of the protective film introduces biodegradable materials such as starch and chitosan, which has two main advantages: First, the adhesive layer has certain adsorption and water absorption properties, and has a certain adhesion to building materials with rough surfaces (such as stones), without the need for additional adhesive, which can effectively reduce construction costs. Second, in asphalt paving construction, the protective film can be used to cover and protect curbstones. Although part of it is buried under the asphalt interface, the buried part can be gradually degraded under the action of microorganisms, reducing adverse effects on the environment.
[0008] The surface of the protective layer is relatively smoother, less likely to adhere to asphalt or dust, and less likely to wrinkle.
[0009] In some preferred embodiments, in order to improve the sunscreen performance of the protective film, an appropriate amount of sunscreen, such as magnesium oxide, zinc oxide or titanium dioxide, can be added to the protective layer. The above inorganic salt type sunscreen can not only improve the sunscreen effect of the protective film, but also appropriately increase the hardness of the protective film and increase the anti-wrinkle performance. In a feasible implementation, the raw material ratio of the protective layer is as follows: 240-260 parts of low-density polyethylene, 4-6 parts of magnesium oxide, zinc oxide or titanium dioxide.
[0010] In some other preferred embodiments, antioxidants or light stabilizers can also be added to the protective layer to improve the sun protection effect and durability of the protective film. In a feasible implementation manner, the raw material ratio of the protective layer is as follows: 240-260 parts of low-density polyethylene and 0.1-2 parts of light stabilizer, and the light stabilizer is selected from any one of a light shielding agent, an ultraviolet light absorber, a quencher and a hindered amine light stabilizer.
[0011] In some specific embodiments of the protective film of the first aspect: The density range of the above-mentioned low-density polyethylene is 0.918~0.935g / cm³.
[0012] The starch is selected from one or a mixture of corn starch, barley starch, oat starch, buckwheat starch, potato starch, tapioca starch, and sweet potato starch; modified starch may also be used, such as microbial fermentation modified starch or oxidative modified starch.
[0013] The cross-linking agent is selected from one of N,N'-methylenebisacrylamide (MBA) and dicumyl peroxide (DCP) or a combination thereof.
[0014] The thickness of the protective film is 25-50 μm, more preferably 30-40 μm. Within this thickness range, the protective film can be extruded and stretched at one time, and the protective film has the best effect of covering curbstones.
[0015] The second aspect of the present invention provides a method for preparing the polymer protective film described in the first aspect, and the preparation method comprises the following steps: fully mixing and grinding the raw material components for preparing the adhesive layer to obtain a premix A, mixing the raw material components for preparing the protective layer to obtain a premix B, and respectively melting the premixes A and B through a single screw and then co-extruding them, and then stretching them into shape.
[0016] The purpose of the present invention is to provide a packaging and protective material for road construction. This packaging material is a consumable. Therefore, cost is the primary factor that needs to be considered in the research and development of the protective film. Polyethylene is a cost-effective and widely available film material. However, the preparation of an integrally formed polyethylene film product with different properties on both sides is still a blank in current research. The design of the present invention adopts multi-layer co-extrusion technology to achieve different properties on both sides of the protective film, but the interlayer adhesion of the co-extruded composite film is generally poor, and it is easy to separate and break at the interface. The design of the present invention adds biomass materials such as starch and chitosan to the adhesive layer, which can not only improve the adsorption and degradability of the adhesive layer, but also the molten material of the adhesive layer and the molten material of the protective layer after compounding still have good compatibility, and good interface compatibility can be achieved by extrusion and stretching.
[0017] In the above preparation method, the preparation method of the premix A is as follows: the starch and chitosan are mixed and then ground at high speed, and then low-density polyethylene and a cross-linking agent are added and continued to be ground at 100-140° C.; the preparation method of the premix B is as follows: low-density polyethylene is ground at high speed at 100-140° C. The above high-speed grinding can be done in a manner such as high-speed shear grinding or ball milling, and the preferred method is ball milling.
[0018] In a specific embodiment, the preparation method of the premix A is as follows: the above-mentioned starch and chitosan are mixed and added to a planetary ball mill, and ground for 25 to 35 minutes, with an orbital speed of 40 to 60 rpm and a rotation speed of 90 to 110 rpm; low-density polyethylene and MBA are added and ball milling is continued for 100 to 140 minutes, and the grinding temperature is 110 to 130°C. At this time, the orbital speed is 90 to 110 rpm and the rotation speed is 180 to 220 rpm.
[0019] In a specific embodiment, the premix B is prepared as follows: low-density polyethylene is added to a planetary ball mill, with an orbital speed of 90-110 rpm and a rotation speed of 180-220 rpm, and high-speed grinding is performed at 100-140° C. for 110-130 min.
[0020] The premix A or B is heated at a uniform rate during the melting process. The melting start temperature is 150°C during feeding, the extrusion temperature is 200°C, and the drawing temperature is not less than 60°C.
[0021] The third aspect of the present invention provides the use of the polymer protective film described in the first aspect as an outdoor packaging material.
[0022] A fourth aspect of the present invention provides an application of the polymer protective film described in the first aspect in the field of road construction. In a more preferred application, the protective film is used to cover and protect curbstones during asphalt pavement construction.
[0023] During the asphalt road construction process, before laying asphalt, the protective film provided by the present invention is covered on the surface of the curbstone, and one side of the adhesive layer contacts the curbstone. Before covering, it is only necessary to remove the dust on the surface of the curbstone, and the protective film can be adhered to the surface of the curbstone by its own adhesion, or the curbstone is moistened. After the protective film absorbs water, it can better exert its viscosity. The construction personnel can add fixings according to the situation. After the covering is completed, the asphalt can be laid. After the asphalt layer is laid, the exposed protective film is torn off.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is designed to provide a polymer protective film material with different characteristics on the inside and outside. The adhesive layer of the protective film material has a certain viscosity, good self-adhesive properties, and can be directly adhered to the surface of the stone. The adhesion increases when it comes into contact with water, and the surface of the protective layer is smoother, not easy to be contaminated by dust, and has good anti-wrinkle and sun protection effects. The polymer protective film can be used as a packaging material at the construction site, and can be packaged without tape or adhesive, and only requires multi-layer winding of the building materials.
[0025] 2. In addition, the present invention introduces biodegradable components into the membrane material, so that the membrane material can be naturally degraded under soil burial conditions. The above characteristics determine that the protective film is particularly suitable as a covering and protective material for curbstones during road paving, and the part remaining under the asphalt can be self-degraded, reducing harm to the environment.
[0026] 3. Multilayer coextrusion is a commonly used composite film preparation method in this field. However, due to the difference in crystallization speed between different film materials, the composite film is prone to interface energy absorption and rupture under external force, and has poor tear resistance. The present invention achieves a close combination of inner and outer film materials by optimizing the raw material formula and preparation process. The protective film has good tensile strength and puncture resistance, filling the technical gap in the development of composite films. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1 Schematic diagram of using a protective film to cover the curbstone during asphalt paving in Example 6; Among them, 1 is the protective film, 2 is the curbstone, 3 is the asphalt pavement, 4 is the interface, and 5 is the pavement base. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] As described in the background technology, in order to provide a covering material more suitable for asphalt pavement paving, the present invention proposes a polymer protective film and a preparation method thereof. In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0032] The reagent models used in the following examples are as follows: Low-density polyethylene: LDPE, brand Q210, melt index 2.1 g / 10min.
[0033] Starch: corn starch.
[0034] Modified starch: Sodium periodate is used to modify corn starch, and the mass ratio of sodium periodate to corn starch is 1:3.
[0035] Chitosan: Deacetylation degree ≥95%, viscosity 100-200 mpa.s.
[0036] Cellulose: colloid, microcrystalline, containing 10.0-20.0% sodium carboxymethyl cellulose as stabilizer.
[0037] Example 1 In this embodiment, a polymer protective film is provided, including an adhesive layer and a protective layer, wherein the raw material ratio of the adhesive layer is as follows: 160 parts of low-density polyethylene, 80 parts of starch, 9 parts of chitosan, and 2 parts of N,N'-methylenebisacrylamide (MBA).
[0038] The raw material ratio of the protective layer is as follows: 260 parts of low-density polyethylene.
[0039] The preparation method of the above polymer protective film is as follows: (1) The raw materials for preparing the adhesive layer are washed with anhydrous ethanol respectively, and placed in a drying oven at 80°C for 10 hours to be fully dried; the starch and chitosan in the above-mentioned portions are fully mixed and ball-milled at an orbital speed of 50 rpm and an autorotation speed of 100 rpm. After ball-milling for 30 minutes, low-density polyethylene and MBA are added and ball-milled for 120 minutes. At this time, the grinding temperature is 120°C, the orbital speed is 100 rpm, and the autorotation speed is 200 rpm; and premix A is obtained.
[0040] (2) The low-density polyethylene used to prepare the protective layer was ball-milled at a grinding temperature of 120° C., an orbital speed of 100 rpm, and a rotation speed of 200 rpm for 120 min to obtain premix B.
[0041] (3) The premix A and premix B are added into two single-screw extruders of a co-extrusion cast composite molding machine. The melting starting temperature of premix A is 150°C. During the process of loading and unloading, each temperature zone is set to 170°C, 190°C, and 200°C, respectively. The loading temperature of premix B is 150°C, and the temperatures of each temperature zone are 165°C, 180°C, and 200°C. After being fully melted, they are extruded through a single-layer die head with a die head temperature of 200°C.
[0042] (4) The film material extruded from the die is stretched on a casting roller. The temperature in the casting area is 65°C. The film thickness after stretching is controlled at 35-40 μm.
[0043] According to the national standard GB / T2790, the peel strength of the adhesive layer is 45.5N / cm, and the peel strength of the protective layer is 19.1N / cm.
[0044] Example 2 In this embodiment, another polymer protective film is provided, comprising an adhesive layer and a protective layer, wherein the raw material ratio of the adhesive layer is as follows: 150 parts of low-density polyethylene, 86 parts of starch, 11.2 parts of chitosan, and 2.8 parts of N,N'-methylenebisacrylamide (MBA).
[0045] The raw material ratio of the protective layer is as follows: 245 parts of low-density polyethylene.
[0046] The preparation method of the above polymer protective film is as follows: (1) The raw materials for preparing the adhesive layer are washed with anhydrous ethanol respectively, and placed in a drying oven at 85°C for 10.5 hours to be fully dried; the starch and chitosan in the above-mentioned portions are fully mixed and then ball-milled at an orbital speed of 40 rpm and an autorotation speed of 90 rpm. After ball-milling for 25 minutes, low-density polyethylene and MBA are added and ball-milling is continued for 100 minutes. At this time, the grinding temperature is 110°C, the orbital speed is 90 rpm, and the autorotation speed is 180 rpm; and premix A is obtained.
[0047] (2) The low-density polyethylene used to prepare the protective layer was ball-milled at a grinding temperature of 110° C., an orbital speed of 90 rpm, and an autorotation speed of 180 rpm for 110 min to obtain premix B.
[0048] (3) The premix A and premix B are added into two single-screw extruders of a co-extrusion cast composite molding machine. The melting starting temperature of premix A is 150°C. During the process of loading and unloading, each temperature zone is set to 175°C, 185°C and 200°C respectively. The loading temperature of premix B is 150°C. The temperatures of each temperature zone are 170°C, 180°C and 200°C. After being fully melted, they are extruded through a single-layer die head with a die head temperature of 200°C.
[0049] (4) The film material extruded from the die is stretched on a casting roller. The temperature in the casting area is 62°C. The film thickness after stretching is controlled at 35-40 μm.
[0050] According to the national standard GB / T2790, the peel strength of the adhesive layer is 33.5N / cm, and the peel strength of the protective layer is 22.1N / cm.
[0051] Example 3 In this embodiment, another double-layer polymer protective film is provided, including an adhesive layer and a protective layer, wherein the raw material ratio of the adhesive layer is as follows: 170 parts of low-density polyethylene, 85 parts of modified starch, 8.2 parts of chitosan, and 2.5 parts of dicumyl peroxide (DCP) as a cross-linking agent.
[0052] The preparation method of the above polymer protective film is as follows: (1) The raw materials for preparing the adhesive layer are washed with anhydrous ethanol respectively, and placed in a drying oven at 90°C for 9.5 hours to be fully dried; the starch and chitosan in the above-mentioned portions are fully mixed and then ball-milled at an orbital speed of 60 rpm and an autorotation speed of 110 rpm. After ball-milling for 35 minutes, low-density polyethylene and MBA are added and ball-milling is continued for 140 minutes. At this time, the grinding temperature is 130°C, the orbital speed is 110 rpm, and the autorotation speed is 220 rpm; and premix A is obtained.
[0053] (2) The low-density polyethylene used to prepare the protective layer was ball-milled at a grinding temperature of 140° C., an orbital speed of 110 rpm, and a rotation speed of 220 rpm for 130 min to obtain premix B.
[0054] (3) The premix A and premix B are added into two single-screw extruders of a co-extrusion cast composite molding machine. The melting starting temperature of premix A is 150°C. During the process of loading and unloading, each temperature zone is set to 172°C, 181°C, and 200°C, respectively. The loading temperature of premix B is 150°C, and the temperatures of each temperature zone are 175°C, 180°C, and 200°C. After being fully melted, they are extruded through a single-layer die head with a die head temperature of 200°C.
[0055] (4) The film material extruded from the die is stretched on a casting roller. The temperature in the casting area is 60°C. The film thickness after stretching is controlled at 35-40 μm.
[0056] According to the national standard GB / T2790, the peel strength of the adhesive layer is 41.8N / cm, and the peel strength of the protective layer is 24.9N / cm.
[0057] Example 4 In this embodiment, another double-layer polymer protective film is provided, which is different from the first embodiment in that the raw material ratio of the protective layer is 241 parts of low-density polyethylene and 4.2 parts of magnesium oxide or zinc oxide.
[0058] Example 5 In this embodiment, another polymer protective film is provided. The difference from the embodiment 1 is that the raw material ratio of the protective layer is 240 parts of low-density polyethylene and 0.3 parts of TINUVIN 791.
[0059] Comparative Example 1 In this embodiment, another polymer protective film is provided, which is different from the embodiment 1 in that the raw material ratio of the adhesive layer is as follows: 160 parts of low-density polyethylene, 60 parts of cellulose, 9 parts of chitosan, and 2 parts of N,N'-methylenebisacrylamide (MBA).
[0060] The preparation method is the same as that of Example 1. After the single-layer die is extruded, the interface adhesion between the protective layer and the adhesive layer is poor, and the minimum thickness after stretching is 52 μm.
[0061] Comparative Example 2 In this embodiment, another polymer protective film is provided, which is different from Embodiment 1 in that the raw material ratio of the adhesive layer is as follows: 160 parts of low-density polyethylene, 65 parts of cellulose, and 2 parts of N,N'-methylenebisacrylamide (MBA).
[0062] The preparation method is as follows: Premix A and premix B were obtained according to the preparation method in Example 1, and premix A and premix B were added to two single-screw extruders of a co-extrusion casting composite molding machine. The starting temperature of the premix A and B was 150°C, and the temperature was increased uniformly from the loading to the unloading process. The temperature in the extrusion zone was 220°C. After being fully melted, they were extruded through a single-layer die head, and the extrusion die head temperature was set to 200°C. After extrusion, the temperature of the casting chill roll was set to 35°C, and the speed was set to 12r / min, so that the extruded A film and B film were fully bonded, and the bonded film was put back into the unidirectional stretching device, preheated at 120°C, and stretched at 150°C, so that the thickness of the stretched film did not exceed 40μm.
[0063] The membrane material prepared by the formula in this embodiment has obvious interface separation between the two layers of the membrane after the first extrusion, and the castability is poor, and it cannot be stretched to less than 40μm. In this embodiment, the thickness of the polymer membrane is reduced to less than 40μm by extending the standing time and performing a second heating stretching method.
[0064] Comparative Example 3 In this embodiment, another polymer protective film is provided, which is different from the embodiment 1 in that the preparation method is as follows: The raw material ratio of the adhesive layer is as follows: 180 parts of low-density polyethylene, 45 parts of chitosan, and 2 parts of N,N'-methylenebisacrylamide (MBA). The rest is the same as in Example 1.
[0065] Performance Characterization For the polymer protective film materials prepared in the above embodiments and comparative examples, their tensile strength, puncture resistance and degradation performance were tested respectively. In the following performance tests, the thickness of each group of film materials was 35±5μm. Since the thickness of the film material in comparative example 1 could not be reduced to less than 50μm, comparative example 1 did not examine the tensile strength and puncture resistance, but only the degradation performance.
[0066] Tensile Strength The membrane materials in the above embodiments and comparative examples were cut into the same size, and their tensile strength, elongation at break and tensile elastic modulus were measured according to the method of national standard GB / T 1040.3-2006. Five samples were collected in each group, and the average measurement results were taken. The results are shown in Table 1 below: Table 1 Tensile strength of membrane materials in Examples 1-5 and Comparative Examples 1-3 According to the above measurement results, the composite of starch and chitosan effectively improves the membrane strength of the polyethylene film after cross-linking. Using high molecular weight raw materials to participate in cross-linking (Comparative Example 2) or using chitosan alone (Comparative Example 3) cannot achieve similar technical effects.
[0067] Puncture resistance According to the method of national standard GB / T 10004-2008, the membrane materials in the above embodiments and comparative examples were tested for puncture strength. The membrane material thickness was 35±5μm, and the membrane material was cut into test pieces with a diameter of 100mm. The puncture speed was (50±5)mm / min, and the maximum load of the steel needle penetrating the membrane was read. Five membrane samples were measured in each group and the average value was taken. The results are shown in Table 2 below: Table 2 Puncture resistance strength of membrane materials in Examples 1-5 and Comparative Examples 1-3 In the above comparative example 1, the thickness of the membrane material cannot be reduced to less than 50 μm, and the measurement results have no comparative significance. The membrane material in comparative example 2 has a greater membrane strength, but the preparation process requires secondary stretching, which is costly. In the comparative example, only chitosan, a biodegradable material, is introduced. Although a dense membrane material can be formed, the strength is also reduced.
[0068] Degradation performance: The degradation performance of the membrane materials in the above examples 1-5 was tested by soil burial method. The above samples were cut into 5×5 cm blocks. The cut films were placed in the laboratory environment and under the soil interface. They were taken out at regular intervals, washed and dried to constant weight, and then weighed. Each group of samples was weighed five times and the average was taken ( W 平均 ). The degradation rate of the membrane material is calculated by the following formula: A %= W 起始 - W 平均 / W 起始 *100%.
[0069] The results are shown in Table 3 below: Table 3 Degradation rate of membrane materials in Examples 1-5 and Comparative Examples 1-3 (ambient temperature 15°C) The membrane materials provided in Examples 1-5 all show good degradation performance. The degradation effect is the worst in the comparative example, which may be related to the thicker membrane thickness. The degradation effect in Comparative Example 2 is also not ideal. The degradation effect of the membrane material in Comparative Example 3 is still somewhat lower than that in Examples 1-5. It is speculated that the number of microorganisms adapted to chitosan is limited, thus reducing the decomposition effect.
[0070] Example 6 In this embodiment, the application of the polymer protective film in the above-mentioned embodiment 1 in the process of paving an asphalt pavement is provided: Figure 1As shown, after the road base 5 is laid, the curbstone 2 is installed. Before the asphalt pavement is laid, the protective film 1 in Example 1 is covered on the surface of the curbstone 2. The side close to the curbstone is the bonding layer, and the side exposed to the outside is the protective layer. When laying asphalt, the dust on the surface of the curbstone 2 is roughly cleaned and the protective film 2 is directly covered on the surface of the curbstone 2. The protective film 2 can be attached to the surface of the curbstone 2 through its own adhesive properties, or the surface of the curbstone 2 can be moistened to increase the adhesion with the protective film 1. After the asphalt is laid to form the asphalt pavement 3, the construction personnel can tear off the exposed protective film from the interface 4, and the part buried under the asphalt can degrade by itself.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polymer protective film, characterized in that: The protective film includes an integrally formed adhesive layer and a protective layer; the raw material ratio of the adhesive layer is as follows: 150-170 parts of low-density polyethylene, 75-86 parts of starch, 8-11.2 parts of chitosan, and 2-6 parts of a cross-linking agent; the raw material of the protective layer includes at least 240-260 parts of low-density polyethylene; The density of the low-density polyethylene ranges from 0.918 to 0.935 g / cm³; The thickness of the protective film is 30-40 μm.
2. The polymer protective film according to claim 1, characterized in that: The protective layer also includes 4 to 6 parts of sunscreen, which is magnesium oxide, zinc oxide or titanium dioxide.
3. The polymer protective film according to claim 1, characterized in that: The protective layer also includes a light stabilizer, and the proportion is as follows: 240-260 parts of low-density polyethylene and 0.1-2 parts of light stabilizer; the light stabilizer is TINUVIN 791.
4. The polymer protective film according to claim 1, characterized in that: The starch is selected from one of corn starch, barley starch, oat starch, buckwheat starch, potato starch, cassava starch, sweet potato starch, modified starch or a mixture of several thereof, and the modified starch is microbial fermentation modified starch or oxidative modified starch.
5. The polymer protective film according to claim 1, characterized in that: The cross-linking agent is selected from one of N,N'-methylenebisacrylamide and dicumyl peroxide or a combination thereof.
6. The method for preparing the polymer protective film according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: fully mixing and grinding the raw material components for preparing the bonding layer to obtain a premix A, mixing and grinding the raw material components for preparing the protective layer to obtain a premix B, and respectively melting the premixes A and B through a single screw extruder, then co-extruding, and drawing to obtain the premix; The preparation method of the premix A is as follows: starch and chitosan are mixed and then high-speed ball milled for 25-35 minutes, the revolution speed is 40-60 rpm, the rotation speed is 90-110 rpm, and low-density polyethylene and a cross-linking agent are added and the ball milling is continued for 100-140 minutes at 100-140° C., the grinding temperature is 110-130° C., the revolution speed is 90-110 rpm, and the rotation speed is 180-220 rpm; The preparation method of the premix B is as follows: low-density polyethylene is subjected to high-speed ball milling at 100-140° C., the grinding time is 110-130 min, the revolution speed is 90-110 rpm, and the rotation speed is 180-220 rpm.
7. The preparation method according to claim 6, characterized in that: The premix A or B is heated at a uniform rate during the melting process, with the initial melting temperature being 150° C. during feeding and the temperature being 200° C. during extrusion.
8. The preparation method according to claim 6, characterized in that: The stretching temperature is 60°C to 65°C and not lower than 60°C.
9. Use of the polymer protective film according to any one of claims 1 to 5 or the polymer protective film prepared by the method according to any one of claims 6 to 9 as outdoor packaging material.
10. Use of the polymer protective film according to any one of claims 1 to 5 or the polymer protective film prepared by the method according to any one of claims 6 to 9 in the field of asphalt pavement paving.
Citation Information
Patent Citations
Stabilizer containing halogen-free flame-retardant hot-melt adhesive membrane for conductive fabric and preparation method of hot-melt adhesive membrane
CN104817969A
Preparation method of polyethylene anticorrosive adhesive tape for underground pipeline
CN106366969A
High-transparency self-adhesive film and processing method thereof
CN112625618A
Die-cutting-resistant self-adhesive glass cover plate protective film and preparation method thereof
CN118956280A